PEMAHAMAN AGAMA DALAM BINGKAI KEBANGSAAN: Studi Kasus pada Organisasi Rohis SMA Negeri 1 Sragen - Rosidin Rosidin; Nurul Aeni (Jurnal Pendidikan dan Kebudayaan, 2017)
Islamic student organization (Rohis) at SMA Negeri 1 Sragen is a media to study Islam for the students. Ideally, the materials given during the learning process should be aligned to nationalism spirit. This study aimed to describe religiosity understanding of the Rohis members in nationalism context and to describe the attitude and behaviors of the Rohis members towards their understanding. This research used qualitative research design. The main primary data was obtained using interview and Focus Group Discussion (FGD) with Rohis members, teachers, and Rohis mentors. Data was analyzed using qualitative analysis. The results show that The Rohis members believe that Islam is the true religion and the belief is followed by the awareness that Ideology of Pancasila recognizes the diversity. Therefore, the idea to establish Islamic country could not be accepted.  Religion understanding of the Rohis members is  implemented by doing the Islamic teachings properly. The difference on faith is not an obstacle for the member of Rohis to interact with other students within and outside the school. The values upheld  is to create unity and harmony are tolerance and respecting others. However, the interaction with the outsiders, particularly that is indicated spreading radicalism among student should be controlled. In conclusion, understanding of the religion of members of Rohis SMAN 1 Sragen is in line with the values of nationality, that is, to keep the unity of the nation. Abstrak: Organisasi Kerohanian Islam (Rohis) di SMA Negeri 1 Sragen adalah salah satu sarana untuk memperdalam Agama Islam bagi para siswa. Secara ideal, pembelajaran agama yang diberikan hendaknya selaras dengan wawasan kebangsaan yang dimiliki oleh Negara Indonesia. Tujuan Penelitian ini adalah menggambarkan pemahaman keagamaan siswa yang mengikuti kegiatan ekstrakurikuler Rohis dalam konteks kebangsaan dan menggambarkan sikap dan perilaku siswa anggota Rohis sebagai bentuk pemahaman tersebut. Penelitian menggunakan pendekatan kualitatif. Data primer didapatkan melalui interviu dan FGD dengan para pengurus Rohis SMA Negeri 1 Sragen serta guru dan pembina Rohis. Analisis data menggunakan metode kualitatif. Hasil penelitian menunjukkan bahwa para pengurus Rohis SMA Negeri 1 Sragen meyakini bahwa Agama Islam merupakan agama yang paling benar dan kesadaran tersebut tetap diikuti dengan kesadaran bahwa Ideologi Pancasila mengakui adanya keragaman dan perbedaan, sehingga ide untuk menjadikan Islam sebagai ideologi negara tidak bisa dibenarkan. Pemahaman agama tercermin dalam perilaku melaksanakan ajaran agama secara benar. Perbedaan keyakinan tidak menghalangi para pengurus Rohis untuk melakukan interaksi dengan siswa lain di lingkungan sekolah maupun luar sekolah. Nilai yang dianut untuk mewujudkan persatuan adalah toleransi dan saling menghormati. Namun, interaksi dengan pihak luar terutama yang terindikasi menyebarkan radikalisme patut diwaspadai. Dengan demikian, pemahaman agama anggota Rohis SMAN 1 Sragen sejalan dengan nilai-nilai kebangsaan, yaitu menjaga persatuan bangsa.